2006
DOI: 10.1055/s-2006-944629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of colonic lesions in cirrhotic patients with portal hypertension

Abstract: Colonic lesions are frequent in cirrhotic patients, but statistical analysis showed that these lesions are not specific for the disease and do not correlate with the etiology and degree of cirrhosis, with the endoscopic treatment of esophageal varices, or with the risk of bleeding from the lower gastrointestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 9 publications
(12 reference statements)
3
44
1
Order By: Relevance
“…These findings were confirmed by an Italian study that reported 54% PHC and 31% CV in cirrhotic patients [7]. This study revealed no relation between the etiology/severity of cirrhosis and the presence of PHC/CV [7].…”
Section: Discussionsupporting
confidence: 77%
“…These findings were confirmed by an Italian study that reported 54% PHC and 31% CV in cirrhotic patients [7]. This study revealed no relation between the etiology/severity of cirrhosis and the presence of PHC/CV [7].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, endoscopic abnormalities in the large bowel of patients with cirrhosis have also been described [3,4,[11][12][13][14]. The spectrum of lesions categorized as portal hypertensive colopathy (PHC) includes findings resembling colitis (edema, diffuse hyperemia, friability, granularity, and/or spontaneous bleeding) and vascular lesions (cherry red spots, telangiectasias, or angiodysplasia-like lesions) [11], although colonic and ano-rectal varices can also be found in up to 31 and 38%, respectively, of cirrhotic patients [3,4].…”
Section: Introductionmentioning
confidence: 87%
“…As in PHG, these lesions are not solely detected in the presence of cirrhosis, but can also be found in cases of extra-hepatic portal vein obstruction [4,12]. Portal hypertensive colopathy seems to be a rare cause of bleeding [3,4].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations